Going green in the maritime industry : a perspective from LNG as marine fuel Part II - Zhao, Yuan (2015)
With increasing concern over the maritime activities on environment, maritime industry is pushed to move towards green shipping. The use of alternative fuels such as liquefied natural gas (LNG) is one of the prevailing measures from technological aspects to reduce pollution. Shipping companies may choose to employ market-based instruments and operational strategies to alleviate environmental impact to tackle the environmental issues as well. However, majority of those measures are indirect and less efficient comparing with technological measures. Hence, the switch to LNG fuel is one of the most optimistic options for most of shipping companies and becomes the focus of our project. Research on LNG as future bunker has seen a strong rise in recent years by various institutes, including classification societies, port authorities and oil majors. This paper seeks to perform a systematic review on LNG as bunker fuel with special focus on technological aspects of LNG fuelled ships, LNG-ready ships, LNG bunkering facilities and other supporting infrastructure. Specific technology deployed, costs incurred, benefits generated and challenges faced by main stakeholders are all discussed. Each chapter also features a mix of viewpoints and concerns from different players in this market.